Sejarah Perkembangan Pemikiran Gerakan Salafiyah - Suhilman Suhilman (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2019)
Salafiyah is reform movement focusing on the matters of akidah and Islamic puritanism. The Islamic teaching should not be treated as a doctrine (das sein) in the society but it should be actualized as stipulated by al-Qur’an and Hadis (das sollen).